(untitled) (Fiep Bulletin - online, 2011)
Several authors state that knowledge production through research can be the more possible way to surpass the logic of repetition. This paper will comment the conception of teachers/students from Gyms for Elderly - ATIs in the perspective of body learning in order to qualify those practices through knowledge reconstruction by research. As a result, we notice that research gets centrality when debating epistemological and cultural matters in ATIs field.